2004
DOI: 10.1165/rcmb.2003-0199oc
|View full text |Cite
|
Sign up to set email alerts
|

Human Airway Trypsin-Like Protease Increases Mucin Gene Expression in Airway Epithelial Cells

Abstract: Human airway trypsin-like protease (HAT) is a serine protease found in sputum of patients with chronic airway diseases and is an agonist of protease-activated receptor-2 (PAR-2). Results from this study show that HAT treatment also enhances mucus production by the airway epithelial cell line NCI-H292 in vitro. Histologic examination showed that HAT enhances mucous glycoconjugate synthesis, whereas the PAR-2 agonist peptide (PAR-2 AP) has no such effect. HAT, but not PAR-2 AP, enhances MUC2 and MUC5AC gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 33 publications
(51 reference statements)
3
70
0
2
Order By: Relevance
“…These phenotypes are associated with the susceptibility of the T3D F S1 gene-encoded 1 protein to cleavage by the pancreatic serine proteases chymotrypsin and trypsin (8,9). While the respiratory tract contains comparably less protease activity than the gastrointestinal tract (47), injury or infection can lead to increases in protease expression in the lung (11,12,(14)(15)(16)(17)23). Inflammation in the respiratory tract may promote reovirus infection through recruitment of leukocytes and increased expression of inflammatory proteases capable of mediating extracellular reovirus disassembly (6,23).…”
Section: Effect Of T3dmentioning
confidence: 99%
See 1 more Smart Citation
“…These phenotypes are associated with the susceptibility of the T3D F S1 gene-encoded 1 protein to cleavage by the pancreatic serine proteases chymotrypsin and trypsin (8,9). While the respiratory tract contains comparably less protease activity than the gastrointestinal tract (47), injury or infection can lead to increases in protease expression in the lung (11,12,(14)(15)(16)(17)23). Inflammation in the respiratory tract may promote reovirus infection through recruitment of leukocytes and increased expression of inflammatory proteases capable of mediating extracellular reovirus disassembly (6,23).…”
Section: Effect Of T3dmentioning
confidence: 99%
“…Although high levels of secreted serine proteases are found in the gastrointestinal tract, protease expression in the respiratory tract is limited in the absence of inflammation (10). Following injury or infection of the respiratory tract, there is increased local expression of serine proteases, matrix metalloproteases, and inflammatory proteases (6,(11)(12)(13)(14)(15)(16)(17). Some of these proteases are capable of catalyzing reovirus uncoating (18-23).…”
mentioning
confidence: 99%
“…14 The largest of the sub-families, HAT/DESC (Differentially Expressed in Squamous cell Carcinoma) consists of the proteases HAT, DESC1-4 10,41,42 and HATlike 3-5. 43 HAT was originally purified from the sputum of patients with chronic airway diseases 24 and is proposed to be associated with mucus production 44 and fibrin deposition within airways. 45 Further, elevated levels of HAT are present in the epidermis of psoriasis patients, suggesting an inflammatory role for this enzyme.…”
Section: The Type II Transmembrane Serine Proteasesmentioning
confidence: 99%
“…First, Dulon and colleagues (54) reported that NE inactivated PAR-2 in A549 and 16HBE14o -cells, and prevented subsequent activation by trypsin, a known agonist for PAR-2. Second, Chokki and coworkers (55) showed that human airway trypsin-like protease, but not a PAR-2-activating peptide, induced MUC2 and MUC5AC gene expression in NCI-H292 cells. Finally, PAR-2 expression was restricted to the basolateral surface of airway epithelial cells (56), which would render it inaccessible to NE released by luminal neutrophils on the apical side of respiratory mucosa.…”
Section: Discussionmentioning
confidence: 99%